Taxonomic revision of the genus Paramunida Baba, 1988 (Crustacea: Decapoda: Galatheidae): a morphological and molecular approach - Cabezas, Patricia; Macpherson, Enrique; Machordom, Annie (Zootaxa, 2010)
The genus Paramunida belongs to the family Galatheidae, one of the most species rich families among anomuran decapod crustaceans. In spite of the genus has received substantial taxonomic attention, subtle morphological variations observed in numerous samples suggest the existence of undescribed species. The examination of many specimens collected during recent expeditions and morphological and molecular comparisons with previously described species have revelaled the existence of eleven new lineages. All of them are distinguished by subtle and constant morphological differences, which are in agreement with molecular divergences reported for the mitochondrial markers ND1 and 16S rRNA. Here, we describe and illustrate the new species, providing brief redescriptions for the previously known species, and a dichotomous identification key for all species in the genus.